قدرة الطلاب على فهم الكلمة المنصرفة فى النص العربي - Huseini Huseini (JURNAL AL-IHDA' : Media Ilmiah Bahasa Arab, 2025)
The basis of writing skills is knowing neuroscience. Because sharaf is the main element for knowing the condition of sentences in Arabic in terms of i'rab and bina, namely the arrangement pattern. Sharaf has a very important role in improving students' ability to write Arabic. The aim of learning sharaf is to enable students to write and understand the position of sentences correctly and also to provide linguistic richness in what they gain from vocabulary, structure and sentence patterns through texts used in lesson materials, applications and exercises. The problem faced by students at the Syamsudhdhuha Islamic boarding school is their lack of ability to read Arabic texts in sentences related to sharaf. The aim of the research is to determine students' abilities in applying sharaf knowledge to Arabic texts and to find out the methods used by teachers in teaching sharaf. The research method used in this research is descriptive analysis method. The population in this study were all aliyah students. The samples taken were all third grade aliyah students. The research tools used by researchers are direct observation, interviews and questionnaires. The results of the research were that private madrasah aliyah students at the Syamsudhdhuha Islamic boarding school were less able to apply sharaf in Arabic texts, and the methods used by teachers in teaching sharaf were still traditional methods.